Pengaruh Mentoring Rohani Islam Dan Karakter Religius Terhadap Hasil Belajar Siswa - Sabila Nurul Azizah; Muhammad Ja’far Nashir; Joko Subando (4, 2025)
In education, student activities are not limited to intracurricular activities but also include extracurricular activities. Intracurricular activities emphasize general knowledge aligned with curriculum objectives, while extracurricular activities support the development of students' interests and talents. One such activity that plays a crucial role is Islamic spiritual mentoring. This study aims to analyze three main points: the relationship between Islamic spiritual mentoring and religious character, the relationship between religious character and learning outcomes, and the relationship between Islamic spiritual mentoring and religious character simultaneously on student learning outcomes. The study used a descriptive quantitative approach with data analysis using Pearson Product Moment Correlation. Islamic spiritual mentoring is considered to have a significant influence on the formation of students' religious character. In this activity, students are not only provided with Islamic guidance but are also guided to practice religious values ​​such as congregational prayer, Quranic recitation, and other worship activities. The religious character formed through this process also supports the improvement of learning quality, both in terms of attitude, motivation, and achievement of learning outcomes. Thus, Islamic spiritual mentoring has a dual role: shaping morals while strengthening students' learning motivation. Good religious character can foster an awareness that knowledge is an essential part of worship. Therefore, the relationship between Islamic spiritual mentoring, religious character, and learning outcomes is closely interconnected and makes a significant contribution to improving student achievement. Abstrak Dalam dunia pendidikan, kegiatan yang dilakukan siswa tidak hanya terbatas pada intrakurikuler, tetapi juga mencakup ekstrakurikuler. Kegiatan intrakurikuler lebih menekankan pada pengetahuan umum yang sesuai dengan tujuan kurikulum, sedangkan kegiatan ekstrakurikuler berfungsi sebagai pendukung untuk mengembangkan minat dan bakat peserta didik. Salah satu bentuk kegiatan yang berperan penting adalah mentoring rohani Islam. Penelitian ini bertujuan untuk menganalisis tiga hal pokok, yaitu hubungan mentoring rohani Islam terhadap karakter religius, hubungan karakter religius terhadap hasil belajar, serta hubungan mentoring rohani Islam dan karakter religius secara bersama-sama terhadap hasil belajar siswa. Penelitian menggunakan pendekatan kuantitatif deskriptif dengan analisis data melalui Korelasi Pearson Product Moment. Mentoring rohani Islam dinilai mampu memberikan pengaruh signifikan terhadap pembentukan karakter religius siswa. Dalam kegiatan ini, siswa tidak hanya diberikan pembinaan keislaman, tetapi juga diarahkan untuk mengamalkan nilai-nilai religius seperti sholat berjamaah, tadarus Al-Qur’an, dan kegiatan ibadah lainnya. Karakter religius yang terbentuk dari proses ini turut mendukung peningkatan kualitas belajar, baik dari sisi sikap, motivasi, maupun pencapaian hasil belajar. Dengan demikian, mentoring rohani Islam memiliki peran ganda, yakni membentuk akhlak sekaligus memperkuat motivasi belajar siswa. Karakter religius yang baik dapat mendorong kesadaran bahwa ilmu adalah bagian penting dari ibadah. Oleh karena itu, hubungan antara mentoring rohani Islam, karakter religius, dan hasil belajar saling berkaitan erat serta memberikan kontribusi nyata terhadap peningkatan prestasi siswa.